The Effect of Vascak-Based Interactive Lecture Demonstration (ILD) Learning on Learning Outcomes is Reviewed From The Attitude of Students - Nursyafarinah, Nursyafarinah; Arsyad, Muhammad; Palloan, Pariabti (Jurnal Pendidikan dan Profesi Keguruan, 2025)
This study aims to analyze the influence of Interactive Lecture Demonstration (ILD) learning based on Vascak media on the learning outcomes of Physics Science at MTs Darusshalihin Berru, Soppeng Regency which was reviewed from the attitude of 47 grade IX students. This type of research is a True Experiment research using two classes as samples, both of which are taught by the Interactive Lecture Demonstration (ILD) learning method of Static Electricity material with different treatments, consisting of a control class using Powerpoint media (conventional) and an experimental class using Vascak media. The instrument used is a learning outcome test containing multiple-choice questions that have been tested for validity and reliability to measure students' Physics Science learning outcomes and an instrument in the form of a student attitude questionnaire with positive attitude and negative attitude categories using cognitive, affective and conactive attitude indicators. Data analysis was carried out by SPSS statistical test using ANOVA which was obtained for the effect of the use of Vascak media on learning outcomes showing a value of F = 20.623 with a value of Sig = 0.000 which was interpreted to have a significant impact. Similarly, the results of attitude testing had a significant effect on learning outcomes as seen from the value of F = 27.112 with Sig = 0.000. However, the two variables did not interact because the significance value obtained was 0.064 > 0.05. This indicates that the Interactive Lecture Demonstration (ILD) learning method based on Vascak media and the attitude of students have a significant effect on the learning outcomes of Science Physics independently because there is no attraction between the two variables.